2019
DOI: 10.1523/eneuro.0317-19.2019
|View full text |Cite|
|
Sign up to set email alerts
|

Apparent Genetic Rescue of AdultShank3Exon 21 Insertion Mutation Mice Tempered by Appropriate Control Experiments

Abstract: SHANK3 (ProSAP2) is among the most common genes mutated in autism spectrum disorders (ASD) and is the causative gene in Phelan–McDermid syndrome (PMS). We performed genetic rescue of Shank3 mutant phenotypes in adult mice expressing a Shank3 exon 21 insertion mutation (Shank3G). We used a tamoxifen-inducible Cre/loxP system (CreTam) to revert Shank3G to wild-type (WT) Shank3+/+. We found that tamoxifen treatment in adult Shank3GCreTam+ mice resulted in complete rescue of SHANK3 protein expression in the brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Our ndings add to the growing concern regarding the interpretation of studies utilizing conditional knockout technology to study the plasticity of behavioral phenotypes associated with ASD. Another recent study reported apparent rescue of behavioral phenotypes in vehicle-treated CAGGs-CreER expressing Shank3 mutants, implicating some baseline behavioral effects produced by the Cre transgene (Speed et al, 2019). An alternative potential reason for the negative results presented in the current study is our inclusion of the appropriate Cre-positive mice that did not receive tamoxifen in our control groups, whereas previous studies did not implement all necessary controls.…”
Section: Discussionmentioning
confidence: 75%
“…Our ndings add to the growing concern regarding the interpretation of studies utilizing conditional knockout technology to study the plasticity of behavioral phenotypes associated with ASD. Another recent study reported apparent rescue of behavioral phenotypes in vehicle-treated CAGGs-CreER expressing Shank3 mutants, implicating some baseline behavioral effects produced by the Cre transgene (Speed et al, 2019). An alternative potential reason for the negative results presented in the current study is our inclusion of the appropriate Cre-positive mice that did not receive tamoxifen in our control groups, whereas previous studies did not implement all necessary controls.…”
Section: Discussionmentioning
confidence: 75%
“…2C-D). Because CRE expression in muscles produced opposite changes in AP firing patterns in strains containing the shn-1 nu697 and nu652 alleles, these results are unlikely to be caused by toxicity associated with CRE expression (Speed et al, 2019). Collectively, these results suggest that SHN-1 acts in body muscles to control AP duration.…”
Section: Shn-1 Acts In Muscles To Regulate Action Potential Durationmentioning
confidence: 74%
“…Avoidance to novelty or inanimate objects was strong in two strains of the model ex4-22|ALL [ 128 , 130 ], which also showed increased escape attempts, but was also consistently described in mice haboring other deletions or mutations such as ex9|ANK [ 82 ], ex11|SH3 [ 123 ], ex13-16|PDZ [ 155 , 160 , 163 , 166 ], ex21|PRO [ 125 , 178 ], and ex21|PRO-InsG3728 [ 126 , 187 ]. It was also observed that targeted KO in somatosensory neurons or cells of the caudal embryo in mice of the strains ex13-16|PDZ-Advillin Cre or -Cdx2 Cre induced such avoidance behavior [ 140 ].…”
Section: Main Textmentioning
confidence: 99%
“…Sensorimotor function is often assessed in tasks such as the rotarod, which primarily targets coordination, by motor reflexes induced through sensory stimuli such as the righting reflex and geotaxis, and by gait analysis. Abnormalities concerning tasks depending on sensorimotor function have been described in SHANK3-deficient rodents of the deletion models ex4-22|ALL [ 128 , 130 ], ex4-9|ANK [ 78 , 124 , 155 , 167 ], ex11|SH3 [ 123 ], and ex13-16|PDZ [ 83 , 155 , 159 , 183 ], or mice harboring schizophrenia- and ASD-associated mutations (ex21|PRO-R1117X, -InsG3680 [ 127 ] or -InsG3728 [ 126 , 187 ]). Notably, single studies did not observe differences between wildtype and mutant mice of some of these strains [ 80 , 90 , 166 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation